Interprofessional Education for Optimizing the Fostering Candidate Pilgrimage Program in Waiting Period to Achieve Istitha’ah - Rachmawati, Ermin; Riskiyah, Riskiyah; Dharma Dewi, Tanaya Jati; Wijaya, Dhani; Syarifuddin, Sadli; Aisa, Amalia Nur; indrawan, Doby (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: The Faculty of Medicine and Health Sciences of the State Islamic University (FKIK UIN) Malang needs to build recognition in realizing its superior curriculum, namely hajj health through hajj pilgrimage interprofessional education (HIPE) course. On the other hand, there is an opportunity from the Batu City Government and Ministry of Religion to collaborate in fostering the waitingperiod of Prospective Hajj Pilgrims (CJH) to achieve istitha'ah.Objective: This study aimed to compile and evaluate the learning instructional design of the Hajj Pilgrimage Interprofessional Education (HIPE) program as a manifestation of the superior curriculum of FKIK UIN Malang which is part of the prospective hajj pilgrimage waiting period program of the Batu city government.Research Method: This research was conducted from June to December 2023. The participants of the study included the executive board of faculty incluring dean and vice dean, head of medical bachelor and bachelor of pharmacy educational program, head of the ministry of religion, the hajj and umrah organization division, head program director of the health service district and from 5 primary health center, along with hajj pilgrimage candidate of Batu city in 2023. The data used was primary data from the program satisfaction survey questionnaire and secondary data in the form of formal documents.Results: The learning instructional design has been approved by the faculty leader, head of medical and pharmacy bachelor program, head of ministry of religion, and head of Batu city health office in Focus Group Discussion meeting with the topic of Hajj Health Superior Curriculum marked by the issuance of the MoU, the organizational structure of the faculty unit called Unit of Medical and Health Profession Education (UMHPE), and the Dean's Decree for the unit in charge. The organizational structure involved all parties including the ministry of religion of Batu city, the health officer and hajj program director in 5 primary health centers in the Batu city, and the Faculty with its study program. Longitudinal courses in 2 bachelor program was arranged with a spiral curriculum entitled HIPE 1, 2, 3. HIPE 3 as the final course applied the Project Based Learning (PJBL) approach providing intervention program to achieve istitha'ah which is implemented through hajj pilgrimage candidate serial home visits. The quality cycle has been applied in the entire series of learning programs. The results of the satisfaction survey from hajj pilgrimage candidate and external stakeholders showed a positive response to the HIPE program and the objectives of HIPE itself.Conclusion: The HIPE learning prototype as a superior curriculum of FKIK UIN Malang to foster hajj pilgrimage candidate during the waiting period in Batu City already facilitated a mutual collaboration between FKIK UIN Malang, the Health Office and the Ministry of Religion of Batu City.